Functional mapping of brain synapses by the enriching activity-marker SynaptoZip. Issue 1 (December 2017) - Ferro, Mattia; Lamanna, Jacopo; Ripamonti, Maddalena; Racchetti, Gabriella; Arena, Alessandro; Spadini, Sara; Montesano, Giovanni; Cortese, Riccardo; Zimarino, Vincenzo; Malgaroli, Antonio
Abstract Ideally, elucidating the role of specific brain circuits in animal behavior would require the ability to measure activity at all involved synapses, possibly with unrestricted field of view, thus even at those boutons deeply located into the brain. Here, we introduce and validate an efficient scheme reporting synaptic vesicle cycling in vivo. This is based on SynaptoZip, a genetically encoded molecule deploying in the vesicular lumen a bait moiety designed to capture upon exocytosis a labeled alien peptide, Synbond. The resulting signal is cumulative and stores the number of cycling events occurring at individual synapses. Since this functional signal is enduring and measurable both online and ex post, SynaptoZip provides a unique method for the analysis of the history of synaptic activity in regions several millimeters below the brain surface. We show its broad applicability by reporting stimulus-evoked and spontaneous circuit activity in wide cortical fields, in anesthetized and freely moving animals. Visualization of synaptic activity in the living brain is challenging. This study devises a simple and efficient scheme that reports synaptic vesicle recycling in vivo using SynaptoZip, a genetically encoded sensor of past synaptic activities.